Spain the best of Spanish interiors, gardens, architecture, landscapes - Mitchell, Angus (Little, Brown, 1990)
Embracing the entire country, this book displays a wide spectrum of Spain's decorative heritage: architectural detail, contrasting views of interiors, cool, scented gardens and the latest ideas from Spain's leading designers.